IDNLearn.com: Your one-stop platform for getting reliable answers to any question. Our experts are ready to provide prompt and detailed answers to any questions you may have.
Sagot :
To find the values of the limits [tex]\(\lim_{x \to -6} f(x)\)[/tex], [tex]\(\lim_{x \to -2} f(x)\)[/tex], and [tex]\(\lim_{x \to 4} f(x)\)[/tex], we need to systematically evaluate each one as [tex]\(x\)[/tex] approaches the given points.
1. Evaluate [tex]\(\lim_{x \to -6} f(x)\)[/tex]:
- As [tex]\(x\)[/tex] approaches [tex]\(-6\)[/tex], we need to determine the behavior of [tex]\(f(x)\)[/tex] near this point.
- The limit essentially captures the value that [tex]\(f(x)\)[/tex] converges to as [tex]\(x\)[/tex] gets arbitrarily close to [tex]\(-6\)[/tex].
Therefore,
[tex]\[ \lim_{x \to -6} f(x) = f(-6) \][/tex]
2. Evaluate [tex]\(\lim_{x \to -2} f(x)\)[/tex]:
- Similarly, as [tex]\(x\)[/tex] approaches [tex]\(-2\)[/tex], we must examine [tex]\(f(x)\)[/tex] in the vicinity of [tex]\(-2\)[/tex].
- We are interested in the value that [tex]\(f(x)\)[/tex] reaches as [tex]\(x\)[/tex] gets very close to [tex]\(-2\)[/tex].
Hence,
[tex]\[ \lim_{x \to -2} f(x) = f(-2) \][/tex]
3. Evaluate [tex]\(\lim_{x \to 4} f(x)\)[/tex]:
- Lastly, as [tex]\(x\)[/tex] approaches [tex]\(4\)[/tex], we analyze [tex]\(f(x)\)[/tex] around this point.
- This limit represents the value [tex]\(f(x)\)[/tex] approaches as [tex]\(x\)[/tex] gets very close to [tex]\(4\)[/tex].
Thus,
[tex]\[ \lim_{x \to 4} f(x) = f(4) \][/tex]
Summarizing our findings,
- [tex]\(\lim_{x \to -6} f(x)\)[/tex] is given by [tex]\(f(-6)\)[/tex]
- [tex]\(\lim_{x \to -2} f(x)\)[/tex] is given by [tex]\(f(-2)\)[/tex]
- [tex]\(\lim_{x \to 4} f(x)\)[/tex] is given by [tex]\(f(4)\)[/tex]
Thus, the evaluated limits are:
[tex]\[ \lim_{x \to -6} f(x) = f(-6), \quad \lim_{x \to -2} f(x) = f(-2), \quad \lim_{x \to 4} f(x) = f(4) \][/tex]
1. Evaluate [tex]\(\lim_{x \to -6} f(x)\)[/tex]:
- As [tex]\(x\)[/tex] approaches [tex]\(-6\)[/tex], we need to determine the behavior of [tex]\(f(x)\)[/tex] near this point.
- The limit essentially captures the value that [tex]\(f(x)\)[/tex] converges to as [tex]\(x\)[/tex] gets arbitrarily close to [tex]\(-6\)[/tex].
Therefore,
[tex]\[ \lim_{x \to -6} f(x) = f(-6) \][/tex]
2. Evaluate [tex]\(\lim_{x \to -2} f(x)\)[/tex]:
- Similarly, as [tex]\(x\)[/tex] approaches [tex]\(-2\)[/tex], we must examine [tex]\(f(x)\)[/tex] in the vicinity of [tex]\(-2\)[/tex].
- We are interested in the value that [tex]\(f(x)\)[/tex] reaches as [tex]\(x\)[/tex] gets very close to [tex]\(-2\)[/tex].
Hence,
[tex]\[ \lim_{x \to -2} f(x) = f(-2) \][/tex]
3. Evaluate [tex]\(\lim_{x \to 4} f(x)\)[/tex]:
- Lastly, as [tex]\(x\)[/tex] approaches [tex]\(4\)[/tex], we analyze [tex]\(f(x)\)[/tex] around this point.
- This limit represents the value [tex]\(f(x)\)[/tex] approaches as [tex]\(x\)[/tex] gets very close to [tex]\(4\)[/tex].
Thus,
[tex]\[ \lim_{x \to 4} f(x) = f(4) \][/tex]
Summarizing our findings,
- [tex]\(\lim_{x \to -6} f(x)\)[/tex] is given by [tex]\(f(-6)\)[/tex]
- [tex]\(\lim_{x \to -2} f(x)\)[/tex] is given by [tex]\(f(-2)\)[/tex]
- [tex]\(\lim_{x \to 4} f(x)\)[/tex] is given by [tex]\(f(4)\)[/tex]
Thus, the evaluated limits are:
[tex]\[ \lim_{x \to -6} f(x) = f(-6), \quad \lim_{x \to -2} f(x) = f(-2), \quad \lim_{x \to 4} f(x) = f(4) \][/tex]
We appreciate your participation in this forum. Keep exploring, asking questions, and sharing your insights with the community. Together, we can find the best solutions. For trustworthy answers, rely on IDNLearn.com. Thanks for visiting, and we look forward to assisting you again.